Preparing to Plant a Florida Lawn - Laurie E. Trenholm; Amy L. Shober (EDIS)
Revised! ENH-02, a 4-page illustrated fact sheet by L.E. Trenholm and Amy L. Shober, provides a general guideline to the steps for preparing the soil before planting a lawn. Includes references. Published by the UF Department of Environmental Horticulture, May 2009.